Experimental Study on the Change Rule of Typical Defective Discharge Characteristics of Transformer Oil Paper Under the Action of Oil Flow Fiber Impurity Particles - Jing Du; Lingyi Wang; Xinrong Chen; Kun Chen; Xu Chen; Guozhi Zhang (IEEE Access)
This paper addresses the issue of fiber impurity particle movement and accumulation on the surface of the electrode at the outlet of the converter transformer during long-term operation, which leads to changes in various local discharge characteristics and mechanisms in the insulating oil. An oil flow device experimental platform was constructed to study the discharge characteristics of fiber impurity particles under different particle concentrations, electrode spacings, and insulating medium conditions. The study found that: 1) The higher the concentration of fiber impurities in the contaminated insulating oil, the easier it is for a complete “impurity bridge” to form between the electrodes. At the same time, the discharge quantity associated with the accumulation of impurities also increases. 2) When the concentration of fiber impurities in the contaminated insulating oil is fixed, as the electrode spacing increases, the number of continuous “fiber impurity bridges” formed between the electrodes decreases sharply, while the discharge quantity increases dramatically. As the thickness of the insulating paperboard increases, the accumulation of fiber impurity particles is reduced, and the discharge signal gradually strengthens.